2013
DOI: 10.1103/physrevlett.110.188101
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic versus Energetic Discrimination in Biological Copying

Abstract: We study stochastic copying schemes in which discrimination between a right and a wrong match is achieved via different kinetic barriers or different binding energies of the two matches. We demonstrate that, in single-step reactions, the two discrimination mechanisms are strictly alternative and can not be mixed to further reduce the error fraction. Close to the lowest error limit, kinetic discrimination results in a diverging copying velocity and dissipation per copied bit. On the opposite, energetic discrimi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
157
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(168 citation statements)
references
References 27 publications
10
157
1
Order By: Relevance
“…The role of energy dissipation in a variety of processes related to biological information processing has received much attention recently [1][2][3][4][5][6][7][8][9][10][11][12][13][14], to give just one class of examples for which one tries to uncover fundamental limits involving energy dissipation in biomolecular systems.…”
mentioning
confidence: 99%
“…The role of energy dissipation in a variety of processes related to biological information processing has received much attention recently [1][2][3][4][5][6][7][8][9][10][11][12][13][14], to give just one class of examples for which one tries to uncover fundamental limits involving energy dissipation in biomolecular systems.…”
mentioning
confidence: 99%
“…The time-error and dissipation-error trade-offs are the same of those obtained by copolymerization models [16]. However, the definition of efficiency allows us to shed new light on this processes.…”
Section: 5] [2] Fig 2(left)mentioning
confidence: 52%
“…In other words, the network topology does not discriminate. According to [16], the substrates discrimination is embedded in the rate constants. Indeed, the substrates are distinguished either because of differences of chemical complex binding energies (the typical example is DNA replication and RNA transcription, in which there is an affinity difference between matching and mismatching nucleotide pairs), or because the activation energies related to the reaction involving the right substrate are lower than for the other ones (figure 2(left), describing the energy landscape of the Michaelis-Menten reaction scheme, can help in visualizing these ideas).…”
Section: Descriptionmentioning
confidence: 99%
“…The study indicates that a sustained non--equilibrium steady state essentially drives the polymerization error rate to transit from a thermodynamically determined value to a kinetically determined one, i.e., the fidelity is achieved under the "flux--driven kinetic checkpoints" 75 . The two discrimination mechanisms involving either energetic (different binding energies) or kinetic (different kinetic barriers) differentiation are also analyzed more recently in 76 . It is shown that though the two mechanisms cannot be mixed in a single--step reaction to reduce errors, they can be combined in coping schemes with error correction through proofreading 76 .…”
Section: Fidelity Control In Single Subunit Polymerasesmentioning
confidence: 99%
“…The two discrimination mechanisms involving either energetic (different binding energies) or kinetic (different kinetic barriers) differentiation are also analyzed more recently in 76 . It is shown that though the two mechanisms cannot be mixed in a single--step reaction to reduce errors, they can be combined in coping schemes with error correction through proofreading 76 .…”
Section: Fidelity Control In Single Subunit Polymerasesmentioning
confidence: 99%